If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(1x + -2) = 49 Reorder the terms: 7(-2 + 1x) = 49 (-2 * 7 + 1x * 7) = 49 (-14 + 7x) = 49 Solving -14 + 7x = 49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 7x = 49 + 14 Combine like terms: -14 + 14 = 0 0 + 7x = 49 + 14 7x = 49 + 14 Combine like terms: 49 + 14 = 63 7x = 63 Divide each side by '7'. x = 9 Simplifying x = 9
| (-6x)+4=0 | | f(x)=1/4x^2-12x | | 5+2x=x+5 | | x^2-mx+3m-9=0 | | -5+6x=-6x+139 | | 15x^-3y^6z^-4/25x^-2y^-2z | | 7/9x3/4= | | 2+5x=x+26 | | 9+x=5x+9 | | 3m-8n/13= | | 5y-25x=20 | | -9-3x=4x+68 | | 3m-8n/13 | | -3x-3=-53+7x | | 2x+4(2x+6)=10x+24 | | 10+3x=-2x-50 | | 5m-8=2m+4 | | 2(x+4)+2=6x+2(x+2) | | 6x-7=5+3x | | -2-4=10-4 | | 2m+4=3m-6 | | x^6-7x^3=18 | | 7x-1=6x-8 | | 3(x-2)=5(2x+3) | | U/3=u/2-4 | | -7x+1=6x+27 | | P=5x+20y | | 5-7x=-5x+17 | | n+m=6 | | -x-1=2x-31 | | 3m+24=25 | | 230=5(6-5n) |